2020
DOI: 10.5771/1615-634x-2020-1-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Nebenbei, mobil und ohne Ziel? Eine Mehrmethodenstudie zu Nachrichtennutzung und -verständnis von jungen Erwachsenen

Abstract: Prozesse der Nachrichten- und Informationsnutzung haben sich in den letzten Jahren gewandelt - insbesondere bei jungen Erwachsenen. So suggerieren die Dominanz des Smartphones sowie die Popularität sozialer Medien in dieser Altersgruppe, dass die Nutzung von Nachrichten zunehmend durch den situativen und sozialen Kontext geprägt sowie abhängig(er) von „zufälligen“ Kontakten mit einzelnen Beiträgen wird. Derzeit fehlt es jedoch an Erkenntnissen dazu, ob und inwiefern sich Zusammenhänge zwischen den Charakterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
9
0
1
Order By: Relevance
“…Incidental exposure versus targeted search for information. Consistent with contemporary findings on young peoples' news habits, participants from the focus groups made up of young adults in particular reported their engagement with 'breaking news' as being incidental (Kümpel 2020) By contrast to their "news-finds-me perception" (Gil de Zúñiga et al 2017: 107), these young adults paid active attention to news and looked for information themselves in the case of current events such as the explosion in Beirut which happened only a few days before group discussions took place. For example, most respondents reported that they incidentally heard about the explosion on social media and used editorial sources for news 'when more information became available' .…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Incidental exposure versus targeted search for information. Consistent with contemporary findings on young peoples' news habits, participants from the focus groups made up of young adults in particular reported their engagement with 'breaking news' as being incidental (Kümpel 2020) By contrast to their "news-finds-me perception" (Gil de Zúñiga et al 2017: 107), these young adults paid active attention to news and looked for information themselves in the case of current events such as the explosion in Beirut which happened only a few days before group discussions took place. For example, most respondents reported that they incidentally heard about the explosion on social media and used editorial sources for news 'when more information became available' .…”
Section: Resultssupporting
confidence: 76%
“…For example, the most preferred news source for teenagers is television and they often use older members of their family and teachers as a conduit for current affairs information (Notley et al 2017). The use of social media platforms leads to rather passive and incidental news behaviour (Kümpel 2020) while providing both generations access to a variety of content from different actors: “information from news media, political actors, and friends and followers blend to create a unique political information diet” (Andersen et al 2020: 138). However, little is known about the relationship between incidental exposure and targeted searches for information in the context of social media platforms.…”
Section: Journalism Young People and News Use In A Hybrid Media Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In many cases, they fill this need by turning to content focused on lifestyle, culture, sports and other topics more closely connected to their own personal interests but not strongly related to politics. These statements reveal how many Swiss youth acknowledge that, on the one hand, they should aspire to be informed citizens, and, on the other hand, their own preferences and usage patterns do not make them informed citizens in the traditional sense (see also Kümpel, 2020). They also reveal how routinised news consumption may be a significant factor in individuals' news consumption, and how these routines have eroded over time.…”
Section: Reasons Behind Swiss Youth's Relatively Low Rates Of News Consumptionmentioning
confidence: 99%